Development of hybrid VANET routing protocol between buses and cars - Phongsathorn Boonnithiphat (2018)
© 2015 IEEE. Currently, VANET has been developed for vehicle-to-vehicle communication (V2V). There is MI-VANET protocol that is developed for packet forwarding using only buses. It has high successful packet delivery rates. However, its performance degrades when the number of buses is low. Therefore, this paper proposes a new hybrid protocol called Hybrid VANET protocol. The protocol finds routes to forward packets considering both buses and cars. Packets are mainly transmitted by buses. If buses are not available, cars are used to assist packet forwarding. The protocol combines with two methods which are routing method and forwarding method. In the performance evaluation, the experimental results show that our proposed protocol has higher successful packet delivery ratio and has less packet delays than MI-VANET.